Respiratory and desiccation constraints during encapsulated intertidal development of the marine gastropod Acanthina monodon. (October 2020) - Chaparro, O.R.; Salas-Yanquin, L.P.; Büchner-Miranda, J.A.; Pechenik, J.A.; Gray, M.W.; Navarro, J.M.; Cubillos, V.M.
Abstract: Acanthina monodon commonly deposits its egg capsules in the intertidal zone. Capsule aerial exposure during low-tide can impact oxygen consumption rates (OCR) of embryos and intracapsular oxygen availability, and expose embryos to desiccation. OCR increased as embryonic development progressed, and was greater when capsules were submerged in seawater than when exposed to air. Oxygen available within the capsule was always less than that available in the immediate external environment, whether capsules were immersed or exposed. The highest internal oxygen concentrations were recorded during periods of air exposure for embryos in more advanced development stages. When exposed to air, capsules lost water the fastest when they contained early embryos, and suffered the highest mortalities following exposure. Collectively, these data suggest that, although encapsulation helps the embryos to develop across wildly fluctuating environmental conditions, the amount of stress the embryos experience will vary depending on their exact positioning within the intertidal zone. Highlights: Capsule arial exposure impact embryos oxygen uptake and intracapsular oxygen availability. OCR was greater when capsules were submerged than during aerial exposure. Intracapsular oxygen was always less than that available in the external environment. Capsules lost water during air exposition the fastest when they contained early embryos. Capsules with earliest embryos exposed to low HR suffered the largest mortalities.